2019
DOI: 10.1177/2309499019867580
|View full text |Cite
|
Sign up to set email alerts
|

Effects of autologous adipose-derived regenerative stem cells administered at the time of anterior cruciate ligament reconstruction on knee function and graft healing

Abstract: Purpose: To compare the healing and clinical outcomes of anterior cruciate ligament (ACL) reconstruction between patients with or without intraoperative administration of adipose-derived regenerative stem cells (ADRC). Methods: Between 2013 and 2014, the outcomes of 20 soccer players undergoing ACL reconstruction using bone–patellar tendon–bone autograft infiltrated with ADRC at the end of the procedure were compared to a historical, matched cohort of 19 soccer players undergoing the same procedure without ADR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 30 publications
0
27
0
1
Order By: Relevance
“…However, there were no clinical differences in the 28-mo follow-up period. Eduard et al [ 115 ] then compared the healing and clinical effects of ACL reconstruction between patients with or without intraoperative ADSCs administration. They followed 20 soccer players who underwent ACL reconstruction using a bone-patellar tendon-bone autograft infiltrated with ADSCs.…”
Section: Adscsmentioning
confidence: 99%
“…However, there were no clinical differences in the 28-mo follow-up period. Eduard et al [ 115 ] then compared the healing and clinical effects of ACL reconstruction between patients with or without intraoperative ADSCs administration. They followed 20 soccer players who underwent ACL reconstruction using a bone-patellar tendon-bone autograft infiltrated with ADSCs.…”
Section: Adscsmentioning
confidence: 99%
“…The search in electronic databases such as PubMed, Embase, and Cochrane Library resulted in 9 clinical trials ( Figure 3 ), including 5 ongoing trials and 4 completed trials [ 112 115 ] (trial details see Appendix), highlighting the ongoing evolution of this field.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…The MSC group showed improved ligament healing, histologic features, and femur-ACL-tibia complex load-to-failure compared with controls. Recently, Alentorn-Geli et al 146 reported on clinical outcomes of 20 soccer athletes undergoing ACL reconstruction using bone-to-bone autograft augmented with adipose tissue and other progenitor cells, collectively termed adiposederived regenerative stem cells. No significant differences were appreciated between the augmented group and a matched cohort (P > .05) at 12-month follow-up.…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%